Investigation of the early-age performance and microstructure of nano-C–S–H blended cement-based materials - He Wei (De Gruyter, 2021)
Nano calcium silicate hydrate (nano-C–S–H) has become a novel additive for advanced cement-based materials. In this paper, the effect of nano-C–S–H on the early-age performance of cement paste has been studied, and some micro-characterization methods were used to measure the microstructure of nano-C–S–H-modified cement-based material. The results showed that the initial fluidity of cement paste was improved after addition of nano-C–S–H, but the fluidity gradual loss increased with the dosage of nano-C–S–H. The autogenous shrinkage of cement paste can be reduced by up to 42% maximum at an appropriate addition of nano-C–S–H. The mechanical property of cement paste was enhanced noticeably after adding nano-C–S–H, namely, the compressive strengths were improved by 52% and 47.74% at age of 1 day and 7 days, respectively. More hydration products were observed and pore diameter of cement matrix was refined after adding nano-C–S–H, indicating that the early hydration process of cement was accelerated by nano-C–S–H. This was mainly attributed to seed effect of nano-C–S–H. The detailed relationship between microstructure and early-age performance was also discussed.